Transient Neonatal Diabetes - Salemi S; Khankeh H (نشریه پرستاری ایران, 1994)
Sarah was  a 22 year old woman who passing her first pregnancy.  The  pregnancy was unplanned and random and she did not know her last menstrual history. He was visited at home by a midwife community health. no important problem was found in his medical history but he was  smoking 20 Cigarettes daily . It was noteworthy that Saeed ,his wife, had transient neonatal diabetes history. Although Sarah did not  request for prenatal care or pernatal but  had too little information about pregnancy and baby care. midwife community health asked him to participate  in  relaxation  and parenthood techniques courses.he received .